Corrosion protection for the oil and gas industry : pipelines, subsea equipment, and structures - Okyere, Mavis Sika (Taylor & Francis, a CRC title, part of the Taylor & Francis imprint, a member of the Taylor & Francis Group, the academic division of T & F Informa, plc, 2018)
Corrosion Protection for the Oil and Gas Industry: Pipelines, Subsea Equipment, and Structures summarizes the main causes of corrosion and requirements for materials protection, selection of corrosion-resistant materials and coating materials commonly used for corrosion protection, and the limitations to their use, application, and repair. This book focuses on the protection of steels against corrosion in an aqueous environment, either immersed in seawater or buried. It also includes guidelines for the design of cathodic protection systems and reviews of cathodic protection methods, materials, installation, and monitoring. It is concerned primarily with the external and internal corrosion protection of onshore pipelines and subsea pipelines, but reference is also made to the protection of other equipment, subsea structures, risers, and shore approaches. Two case studies, design examples, and the author's own experiences as a pipeline integrity engineer are featured in this book. Readers will develop a high quality and in-depth understanding of the corrosion protection methods available and apply them to solve corrosion engineering problems. This book is aimed at students, practicing engineers, and scientists as an introduction to corrosion protection for the oil and gas industry, as well as to overcoming corrosion issues.
Keywords: Offshore structures -- Corrosion.; Offshore structures -- Protection.; Offshore oil well drilling -- Equipment and supplies -- Protection.; Corrosion and anti-corrosives.; elektronické knihy; electronic books